Serum VEGF-A as a marker of endothelial dysfunction in children with acute lymphoblastic leukemia and pulmonary complications - N.I. Makieieva; V.A. Koval; T.A. Kondratiuk; T.V. Gorbach (Zaslavsky O.Yu., 2023)
Background. Endothelial dysfunction (ED) is common in acute leukemia patients. The study of ED can provide more information about pathological processes in lungs of children with acute lymphoblastic leukemia (ALL). The purpose of the study is to assess the levels of vascular endothelial growth factor A (VEGF-A) and its prognostic value for pulmonary complications in children with ALL. Materials and methods. The control group consisted of 15 healthy children. The level of VEGF-A in serum was assessed by enzyme-linked immunosorbent assay. Results. Pulmonary complications were common in the examined children with ALL, among them: аcute bronchitis (23), recurrent episodes of acute bronchitis (5), pneumonia (18), wheezing (9), bronchial asthma (3), interstitial pneumonia (1), pleurisy (1), pneumothorax (3), lung fibrosis (2), respiratory failure (6). The frequency of pulmonary complications was 82.5 % during chemotherapy protocols and 20.0 % in ALL survivors after a complete course of chemotherapy. Statistically significant increase in VEGF-A level in groups 1 (180.41 (158.16; 200.00) pg/ml) and 2 (165.61 (131.65; 198.45) pg/ml) compared to controls (130.65 (129.45; 132.15) pg/ml) has been detected (p1-C = 0.000011; p2-C = 0.007009). There were no significant differences in VEGF-А levels between children from experimental groups (p1-2 = 0.338394). According to receiver operator characteristic (ROC) analysis, the level of VEGF-A > 198.34 pg/ml after the complete course of chemotherapy can predict the presence of pulmonary complication in ALL survivors (area under the ROC curve 0.965; sensitivity 100.00 %; specificity 89.47 %). Conclusions. Children with ALL have significant ED. The level of serum VEGF-A can be predictive for pulmonary complications in ALL survivors.